2020
DOI: 10.5897/jhf2019.0618
|View full text |Cite
|
Sign up to set email alerts
|

Screening of tree seedling survival rate under field condition in Tanqua Abergelle and Weri-Leke Weredas, Tigray, Ethiopia

Abstract: Rehabilitation of degraded lands through plantations is at the frontline of natural resource management in Ethiopia. However, plantations have been faced with various challenges mainly attributed to poor survival rate of tree seedlings. Hence, this research was conducted in Tanqua 'Abergelle and Weri Leke Wereda's with the objective of screening tree seedlings for their survival rates under field conditions. Tree seedlings that were mostly produced in nurseries of the Woredas were first identified and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This suggests that the area that the forest covers is expanding faster than before. However, as indicated in Figure 3, the rate of plantation is decreasing gradually, and the land cover expansion was not found as expected due to poor survival rate of seedlings, prolonged dry season, water scarcity, and unsustainable management of plantations [23][24][25]. Forest cover increased in some areas after watershed management programs launched in 2011 along with the establishment of eucalyptus plantations [26].…”
Section: Linking Lulc With Biophysical Conservation Effortsmentioning
confidence: 90%
“…This suggests that the area that the forest covers is expanding faster than before. However, as indicated in Figure 3, the rate of plantation is decreasing gradually, and the land cover expansion was not found as expected due to poor survival rate of seedlings, prolonged dry season, water scarcity, and unsustainable management of plantations [23][24][25]. Forest cover increased in some areas after watershed management programs launched in 2011 along with the establishment of eucalyptus plantations [26].…”
Section: Linking Lulc With Biophysical Conservation Effortsmentioning
confidence: 90%
“…For example, Amha et al (2020), revealed that the survival rates of all tree and shrub species decreased considerably over time due to extended dry seasons and termite incidence in severely degraded landscapes in the west Showa Zone of Oromiya regional state, central Highlands of Ethiopia. Likewise, Gebrekidan et al (2020), showed that a reduced seedling survival rate from the first to the next inventory (within four months) was observed in Tanqua, Abergelle, and Weri-Leke districts, Tigray, Ethiopia, which may be attributed to poor management (animal trampling and browsing), moisture stress, and termites. A decreased survival rate of Prunus africana seedlings (from the 1 st to the 5 th year after plantation) was also documented over time in the Ethiopian highlands (Abraham, 2018).…”
Section: Factors Affecting the Early Survival Of Tree Seedlings In Re...mentioning
confidence: 99%
“…Moreover, Preece et al (2023), pointed out that lack of watering seedlings or saplings immediately prior to planting, careless planting in the wrong pit condition, and weed suppression are critical factors that affect plant survival rates in the tropics. For example, the poor survival rate is a common problem, particularly in dry areas of Ethiopia (Gebrekidan et al, 2020) and the Sekota district, northeastern Amhara, Ethiopia (Eshetie et al, 2020). A poor seedling survival rate of less than five percent is also observed in some micro-watersheds in the Southern Nations, Nationalities, and Peoples' Regional State (SNNPR) of Ethiopia (Wolancho, 2015).…”
mentioning
confidence: 99%
“…The survival rate of planted seedlings has proven to be the most important key indicator of the success of forestry activities (Sullivan et al 2009). In addition, inappropriate species selection in afforestation or restoration is the cause of the low survival rate of seedlings (Abrha et al 2020). Information on suitability and patterns of species distribution is crucial for developing future conservation plans (Elith et al 2011).…”
Section: Soil Characteristicsmentioning
confidence: 99%